Successful robotic surgery for primary resection of a vaginal leiomyosarcoma: A case report - Jennifer Hagen; Annelise Wilhite; Maryna Tarbunova; Britt Erickson (Elsevier, 2019)
Primary vaginal leiomyosarcoma (LMS) is a rare entity with limited data on optimal treatment approach. Most previously reported cases utilize an open or transvaginal surgical approach for primary tumor resection. Minimally invasive surgery is an important tool in complex pelvic surgery and the limits of its utility continue to expand. Here, we report a rare case of an 11.7 cm primary vaginal LMS in a 45-year-old female that was successfully resected with a robotic approach. Our case demonstrates an innovative use of the robot and the feasibility and efficacy of this approach for primary resection of large vaginal tumors.